FLAVONOIDS FROM SOME MEDICINAL PLANTS IN VIVO AND IN VITRO - TAMANNA TALREJA,; LALITA YADAV,; KALPANA SHARMA,; ASHA GOSWAMI, (The Bioscan, 2011)
Unorganized cultures of medicinally useful plants Aegle marmelos, Cocculus pendulus, Moringa oleifera and Tinospora cordifolia were established on MS medium supplemented with suitable combinations and concentrations of growth regulators, using seeds as explant in the case of A. marmelos and M. oleifera, nodal explant in C. pendulus and inflorescence explant in T. cordifolia. Plant parts as well as calli of all selected plant species were analyzed for antimicrobial principle. TLC, Spectrophotometry and infra-red spectral studies were used for qualitative and quantitative estimation of flavonoids. Presence of Kaempferol and Quercetin in all four selected plant species was confirmed with significantly higher amount in calli than plant parts in all. Crude extract of flavonoids, extracted from selected plant species and calli, were tested for their antimicrobial activity against Gram-positive bacteria Bacillus subtilis, Staphylococcus aureus, Gram-negative bacteria Escherichia coli, Klebsiella pneumoniae and fungal pathogen Candida albicans. Flavonoid extracted from calli of all plant species showed greater antimicrobial activity against microorganisms because of higher concentrations of flavonoids in them.